RCEP-Countries create Asia-Pacific free trade zone: Trade facilitation but no integrated bloc - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2021)
The signing of the Regional Comprehensive Economic Partnership (RCEP) on 15 November 2020 establishes the world's largest free trade area. The agreement was hailed as an important step forward for the international trade system: protectionism is no longer the only visible option for the third decade of the twenty-first century. But RCEP is a relatively weak instrument. It consolidates existing trade agreements in the region, but does not represent a breakthrough to a liberal economic space. It lacks the potential to make the Asia-Pacific region into a monolithic trading bloc, nor does it contribute to overcoming growing political tensions in the Indo-Pacific.
Keywords: 320